Culturally Relevant Pedagogy and Multi-Belief Learning: Exploring Students’ Experiences of and Perspectives on the Family Project in the GMGY Curriculum. - Malone, Tara (Marino Institute of Education, 2019)
Irish classrooms are increasingly diverse in terms of cultures, languages, ethnicities and religions. Educators can engage with meaningful and relevant cultural elements from their students’ lives, and this can increase student engagement and academic achievement (Gay, 2002). This is referred to as culturally relevant pedagogy (Ladson-Billings, 1995). Community National Schools (CNS) are multi-denominational primary schools which can facilitate culturally relevant pedagogy through their multi-belief programme entitled Goodness Me Goodness You. A feature of this curriculum is the Family Project, which encourages students to discuss their beliefs with their families, and then present these beliefs to their classmates. In this way, aspects of students’ cultures are brought into the classroom. The purpose of this research is to investigate students’ experiences of and perspectives on the Family Project. A mixed-methods research design and an interpretivist paradigm was adopted for this thesis. The main findings reveal that multi-belief learning through listening to one another’s Family Projects was a positive experience for most students. Participants found value in sharing beliefs, particularly for developing religious literacy and intercultural competence, as well as strengthening inter-religious friendships. Many students experienced increased self-esteem as they shared their expertise and were able to “teach the teacher”. However, the majority of students disliked or felt ambivalent towards presenting their own beliefs. Some pupils from minority belief systems experienced a sense of exclusion during multi-belief learning and some felt that the Family Project emphasised differences amongst friendship groups. The thesis concludes by offering recommendations to educators and policymakers for future planning to facilitate multi-belief learning.
Keywords: Research Subject Categories::SOCIAL SCIENCES; Irish classrooms; Pedagogy; Educators; Community National Schools (CNS); multi-denominational primary schools; Multi-belief programme